(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Insights into the Vatican Trial against Cardinal Becciu and Others ABSTRACT: This paper examines various aspects of the trial recently concluded before the Vatican Court, primarily focusing on the determination of criminal liability related to the acquisition of the London Palace on Sloane Avenue with funds from the Secretariat of State. Specifically, the analysis focuses on some key principles stemming from the international commitments made by the Holy See on behalf of the Vatican State, highlighting the resulting constraints on the Pope’s authority as the temporal sovereign of the State. It explores the application of these principles within the trial proceedings and the impact of multiple pontifical rescripta issued during the case, which expanded the powers of the Promoter of Justice in relation to the accused and were justified by the Vatican Court. Additionally, it addresses the potential consequences stemming from these developments, both in terms of the credibility of the Vatican jurisdiction in the international context and in its relations with Italian authorities. SOMMARIO - 1. Premessa: il processo e lo Stato vaticano - 2. L’ordinamento vaticano e la Convenzione europea dei diritti dell’uomo - 3. La Convenzione monetaria e i suoi allegati: effetti nell’ordinamento vaticano - 4. I principi della Convenzione europea e i limiti della potestà del papa come sovrano temporale - 5. Stato vaticano e Stato della Chiesa: due realtà storiche incomparabili - 6. Lo Stato della Città del Vaticano come Stato di diritto - 7. L’art. 6 (Diritto ad un equo processo) della CEDU nell’ordinamento vaticano - 8. L’indipendenza della giurisdizione vaticana: una questione aperta - 9. I rescripta pontifici e la loro incidenza nel processo - 10. I rescripta pontifici e la loro legittimazione da parte del Tribunale vaticano - 11. L’indipendenza dei giudici come requisito essenziale di uno Stato di diritto - 12. Indipendenza della giurisdizione e clausola del foro vaticano - 13. Indipendenza dei giudici vaticani e rapporti di collaborazione con le autorità italiane - 14. Indipendenza dei giudici e riconoscimento in Italia di sentenze straniere - 15. Riconoscimento in Italia di sentenze vaticane e principi della CEDU - 16. Osservazioni conclusive.